PERTANGGUNGJAWABAN HUKUM ATAS DUGAAN PENYIKSAAN OLEH ATASAN MILITER: ANALISIS KASUS KEMATIAN PRAJURIT DI PAPUA - TRISNO SUSETYO, DANNY; RATNA FEBRIYANTI, WIWIN DWI (Universitas Borneo Tarakan, 2025)
The military criminal case concerning the death of Sergeant MBP involved two Army officers, Second Lieutenant (Inf) NS and Second Lieutenant (Inf) MSP, who were charged with committing joint assault resulting in death. At the first instance, the Jakarta Military Court II-08, through Decision Number 163-K/PM.II-08/AD/VI/2022, imposed imprisonment and additional penalties on the defendants. This decision was subsequently appealed. The Jakarta High Military Court, in its ruling, partially upheld the judgment of the lower court while adding an additional penalty of dismissal from military service. The panel of judges considered that the defendants’ actions not only caused the legal consequence of the victim’s death but also had a serious impact on discipline, honor, and the image of the Indonesian National Armed Forces (TNI). Therefore, in addition to the principal sentence of seven (7) years’ imprisonment, the court also imposed the supplementary punishment of dismissal from military service. This ruling reflects that the military court places equal emphasis on the enforcement of criminal law and the preservation of military discipline and morality as primary considerations. The case also stands as an important precedent regarding the application of supplementary punishment in military criminal cases, as it directly affects the dignity of the institution and the sense of justice within society.